2020
DOI: 10.1200/jco.2020.38.15_suppl.7507
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy of the first-in-class anti-CD47 antibody magrolimab combined with azacitidine in MDS and AML patients: Phase Ib results.

Abstract: 7507 Background: Magrolimab (Hu5F9-G4) is an antibody blocking CD47, a macrophage immune checkpoint and don’t eat me signal on cancers. It induces tumor phagocytosis and eliminates leukemia stem cells. Azacitidine (AZA) synergizes with magrolimab by inducing eat me signals on leukemic cells, enhancing phagocytosis. We report Ph1b data including a potential MDS registration cohort. Methods: Magrolimab+AZA was given to untreated intermediate to very high risk IPSS-R MDS and intensive chemo unfit AML patients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 0 publications
0
64
0
1
Order By: Relevance
“…Preliminary data from a phase Ib trial of 68 HMA-naive patients (39 MDS and 29 AML) treated with magrolimab + AZA showed an ORR of 91% (30 out of 33 evaluable patients) in MDS with 42% CR rate, a median duration of response that has not been reached at 5.8 months of median follow up, and a 100% 6-month OS estimate. 108 Notably, even in patients with TP53 mutations, ORR of 75% in both the AML and MDS patient cohort with 6-month OS estimates of 91% and 100%, respectively, have been shown. 108 Since CD47 is also expressed on erythrocytes and erythrocyte precursor cells, hemolytic anemia can be an on-target, off-leukemia adverse event seen with magrolimab.…”
Section: Treatment Options For the Hma Resistant Patientmentioning
confidence: 95%
See 3 more Smart Citations
“…Preliminary data from a phase Ib trial of 68 HMA-naive patients (39 MDS and 29 AML) treated with magrolimab + AZA showed an ORR of 91% (30 out of 33 evaluable patients) in MDS with 42% CR rate, a median duration of response that has not been reached at 5.8 months of median follow up, and a 100% 6-month OS estimate. 108 Notably, even in patients with TP53 mutations, ORR of 75% in both the AML and MDS patient cohort with 6-month OS estimates of 91% and 100%, respectively, have been shown. 108 Since CD47 is also expressed on erythrocytes and erythrocyte precursor cells, hemolytic anemia can be an on-target, off-leukemia adverse event seen with magrolimab.…”
Section: Treatment Options For the Hma Resistant Patientmentioning
confidence: 95%
“… 108 Notably, even in patients with TP53 mutations, ORR of 75% in both the AML and MDS patient cohort with 6-month OS estimates of 91% and 100%, respectively, have been shown. 108 Since CD47 is also expressed on erythrocytes and erythrocyte precursor cells, hemolytic anemia can be an on-target, off-leukemia adverse event seen with magrolimab. 111 However, the combination of AZA + magrolimab appeared to have a safety profile similar to that of AZA monotherapy with anemia (38%), fatigue (21%), neutropenia (19%), and thrombocytopenia (18%) being the most common treatment-related adverse events with only one patient discontinuing treatment due to adverse events.…”
Section: Treatment Options For the Hma Resistant Patientmentioning
confidence: 95%
See 2 more Smart Citations
“…However, monoclonal antibodies are sometimes handicapped by their mechanism of action, in that their biodistribution could lead to an unfavorable pharmacokinetic profile, bottlenecking clinical efficacy. Indeed, though CD47 blockade therapies have achieved early therapeutic efficacy in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) patients in clinical trials ( 79 , 80 ), this strategy has so far struggled in coping with solid tumors. Furthermore, it is possible that monotherapy acting on a single target is simply insufficient to overcoming the heterogeneous tumor microenvironment ( 81 ).…”
Section: Phagocytosis Checkpoint Blockadementioning
confidence: 99%